2022
DOI: 10.1109/access.2022.3196356
|View full text |Cite
|
Sign up to set email alerts
|

Brachial Plexus Nerve Trunk Recognition From Ultrasound Images: A Comparative Study of Deep Learning Models

Abstract: Brachial plexus block is a common regional anesthesia method widely used in upper limb surgery. Nowadays, ultrasound-guided brachial plexus block has been extensively used in clinical anesthesia. However, accurate brachial plexus block is highly dependent on the physician's experience, and a physician without extensive clinical experience may cause nerve injury when performing a nerve block. With the development of artificial intelligence technology, the deep learning method can automatically identify the brac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Early approaches, most published before 2016–17, typically involved steps of feature extraction from the ultrasound image, followed by classification of these features, for both PNB 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 and CNB. 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 Around this point, there has been an increase in published data where the dominant technique was deep learning for both PNB 9 , 11 , 12 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 and CNB, 7 , 74 , 75 , …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Early approaches, most published before 2016–17, typically involved steps of feature extraction from the ultrasound image, followed by classification of these features, for both PNB 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 and CNB. 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 Around this point, there has been an increase in published data where the dominant technique was deep learning for both PNB 9 , 11 , 12 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 and CNB, 7 , 74 , 75 , …”
Section: Resultsmentioning
confidence: 99%
“…In the available sources, a variety of human image interpretation was used as the ground truth. This included a range in the number of humans used in the ground truth from one, 7 , 23 , 24 , 25 , 31 , 32 , 34 , 35 , 36 , 38 , 46 , 49 , 58 , 60 , 67 , 72 , 77 two, 8 , 9 , 19 , 21 , 26 , 30 , 33 , 44 , 61 three, 51 , 52 , 53 , 63 , 65 and up to 15. 48 Some sources cited ‘multiple’ humans, used a plural term (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 However, successful SCB requires skilled ultrasound manipulation such as tilting the probe to obtain an optimal ultrasound view. 3 Previous studies showed the AI-based CADx systems for the segmentation and detection of the brachial plexus, or its identification at the interscalene level [4][5][6][7][8] , however, it simply focused on recognizing the location of anatomical structures on ultrasound. The proposed methods describe the development of deep learning-based CADx systems that can distinguish between optimal and non-optimal views for ultrasound-guided SCB.…”
Section: Introductionmentioning
confidence: 99%